The crystal structure of bis(tetramethylammonium) (di-μ2-aqua)hexaaqua-dibarium(II)) decavanadate - Jiang Yushan; Liu Xinqi; Yu Jiaxun; Liu Yijun; Li Yuanzhe; Wang Heting; Huang Jingru; Huang Xianqiang (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C4H20O18V5BaN, orthorhombic, Pnnm, a = 16.2079(17) Å, b = 9.4181(7) Å, c = 12.4399(9) Å, V = 1898.9(3) Å3, Rgt (F) = 0.0538, wRref (F 2) = 0.0830, T = 298 K.